The relationship of knowledge and application of balanced nutrition messages in adolescents in the Prevention of Iron nutritional Anemia - Agustina (CV. AFDIFAL MAJU BERKAH, 2022)
Anemia in adolescent girls is one of the problems of Public Health, which requires prevention and prevention as possible, because it can reduce immunity and human quality in the next generation. This study aims to determine the prevalence of anemia incidence and classification, the relationship of iron nutrition anemia knowledge, balanced nutrition knowledge and the application of balanced nutrition messages to anemia in young women using quantitative metho ds, cross-cectional design. Samples of students of Depok 6 Public High School numbered 394 people. Collecting data with questionnaires, examining hemoglobin levels with a Hb Quick Check tool. Measurement of height with microtoise and weight with digital scales of HN 289. This study showed that the prevalence of anemia was 46.4%, classification of anemia was 8.6%, anemia was 20% and anemia was mild 17.8%. Knowledge of iron deficiency anemia was quite 67.3%, balanced nutrition knowledge was quite 51.3%. The application of balanced nutrition messages that are not yet in accordance with PGS 64%, There is a significant relationship between balanced nutrition knowledge, application of balanced nutrition messages to iron nutrition anemia, (P <0.05), no correlation between anemia knowledge and iron nutrition anemia (P> 0.05) . Keywords: Balanced